The waist-hip ratio: a flawed index - Richard Francis Burton (Taylor & Francis Group, 2020)
The waist-hip ratio, namely waist circumference (WC) divided by hip circumference (HC), has been referred to in thousands of articles, generally as a correlate and predictor either of health conditions such as cardiovascular disease and diabetes, or of amounts of visceral and subcutaneous abdominal fat. It has been argued that combining WC and HC as a ratio is inappropriate, and yet their individual roles can only be fully elucidated if considered jointly. Whereas WC is positively associated with cardiovascular disease, diabetes and premature mortality, the opposite is true of HC. With health-related measures taken as dependent variables, the present novel approach establishes that WC and HC are far better treated as separate independent variables in multiple regression equations than as their ratio. This necessarily produces closer fits to data. One should then allow for variations in height, or some other such measure of general body size, by including this in the regression equations. The widespread concern with the ratio seems to have distracted attention from HC, for this is discussed notably less often than WC. Given that other body parts, such as the thighs, may share relevant properties with the hips, measurements of these could perhaps replace HC.